Comparative Study of Malacofauna on Three Species : Marrubium vulgare L. (Lamiaceae) Juniperus oxycedrus L. (Cupressaceae) and Cistus salvifolius L. (Cistaceae) in the Mounts of Tlemcen (Oranie, Algeria) - Damerdji, Amina (European Journal of Applied Sciences, 2023)
The region of Tlemcen is located in the North-West of Algeria, whose climatic impact is reflected in the degradation of the forest into matorral, an open formation made up of plant species such as: Cistaceae, Lamiaceae (horehound, stoeckade lavender) and the juniper… We propose to carry out an approach of the diversity of the malacofauna found on 3 plants species namely Marrubium vulgare (Lamiaceae), Juniperus oxycedrus (Cupressaceae) and Cistus salvifolius (Cistaceae).The malacological richness is estimated at11for Cistus 9 for oxycedar juniper and 7 for horehound. It is divided into 4 families: Milacidae, Sphincterochilidae, Helicidae and Subulinidae.Two species of Milacidae are found on the oxycedar.The Sphincterochilidae family with Sphincterochila candidissima is present only on Cistus salvifolius. The Subulinidae has only one species, being Rumina decollata. Concerning the family of Helicidae, the most diversifid has 2 subfamilies: those of Helicinae and Helicellinae. The 1st sub-family has 6 species on oxycedar and 5 species on horehound. The 2nd subfamily includes only one species, namely Helicella terveri on horehound. The seasonal distribution according to the specific richness of Gastropods is shown. We are looking for the malacological species specific to each of the three plant species and the species that are common to them. Finally, the vertical distribution of gastropods is given.